2020
DOI: 10.31235/osf.io/6yw9r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How the coronavirus crisis affects citizen trust in government institutions and in unknown others – Evidence from “the Swedish Experiment”

Abstract: We study how Swedish citizen updated their institutional and interpersonal trust as the corona crisis evolved from an initial phase to an acute phase in the spring of 2020. The study is based on a large web-survey panel with adult Swedes (n = 11,406) in which the same individuals were asked the same set of questions at two different time points during the coronavirus pandemic (t0 and t1). The sample was self-selected but diverse (a smaller subsample, n = 1,464, was pre-stratified to be representative of the Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 26 publications
4
26
3
Order By: Relevance
“…Evidence from panel data from the Netherlands also shows that the lockdown did not increase trust, but it was a rally effect caused by the rising numbers of those with the virus ( Schraff, 2020 ). A panel study from Sweden shows that the increased trust in government influenced interpersonal trust rather than the reverse ( Esaiasson et al, 2020 ), supporting previous panel studies on this question more generally (e.g. Sønderskov and Dinesen, 2016 ).…”
Section: Studies Of Trust and Coronavirus: A Reviewsupporting
confidence: 78%
“…Evidence from panel data from the Netherlands also shows that the lockdown did not increase trust, but it was a rally effect caused by the rising numbers of those with the virus ( Schraff, 2020 ). A panel study from Sweden shows that the increased trust in government influenced interpersonal trust rather than the reverse ( Esaiasson et al, 2020 ), supporting previous panel studies on this question more generally (e.g. Sønderskov and Dinesen, 2016 ).…”
Section: Studies Of Trust and Coronavirus: A Reviewsupporting
confidence: 78%
“…However, we have evidence pointing in the opposite direction from Sweden and Italy where social trust seems to have increased during the lockdown (Demos & PI 2020;Esaiasson et al 2020) relatively to the level it was some time before the pandemic broke out. In addition, a study that compares areas with high social capital with areas with low social capital in seven European countries, including Italy, finds that COVID-19 cases have been increasing faster in the areas with low social capital (Bartscher et al 2020).…”
Section: Testing For Inverse Causalitymentioning
confidence: 75%
“…In two preliminary studies on individual perceptions and awareness during the early stage of Covid-19 in the US and Finland, the trust and confidence in political authorities’ actions to prevent the outbreak was quite low [ 1 , 25 ] while more recent studies showed that the implementation of restrictive measures increased trust in the government, especially for individuals who didn’t experience the disease, directly or indirectly [ 26 , 27 ]. An interesting study conducted in Serbia during the first wave of the Covid-19 pandemic assessed the influence of conspiracy beliefs and political trust on adherence to COVID-19 preventive behaviour [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in addition to the direct effect of risk perception on intentions to limit one’s behavior [ 3 , 5 , 6 , 23 ], we expected a mediating role of the (interpersonal and institutional) trust variable on this relationship [ 24 , 25 , 26 , 27 , 28 ]. Thus, we expected that an increase in risk perception would correspond to an increase in precautionary behavior intentions in the participants, at the same time as an increase in the trust component (interpersonal and institutional).…”
Section: Introductionmentioning
confidence: 99%